2018
DOI: 10.3389/fchem.2018.00042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Selenite on the Nutrient Components of Turnip (Brassica rapa var. rapa Linn.)

Abstract: We administered foliar applications of 50, 100, and 200 mg L−1 selenium (Se, selenite) on turnip (Brassica rapa var. rapa Linn.) and detected the changes in the main nutrient components in fleshy roots. Results showed that the foliar application of Se (IV) significantly increased the Se content in turnip, and Se (IV) positively affected the uptake of several mineral elements, including magnesium, phosphorus, iron, zinc, manganese, and copper. Se (IV) treatments also improved the synthesis of protein and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The most important nutrients that have been investigated in several biofortification studies include calcium [106], iron [92,107], copper [108], zinc [109][110][111], iodine [29,92], potassium [112], and selenium [66,113]. The use of Se fertilizers is one of the most common methods for Se-biofortification of several crops [105], such as rice [113][114][115], maize [116,117], wheat [92,111,118], cowpea [119], potato [85,120], carrot [90,121], turnip [122,123], shallot [124], beans [125], lettuce [91,126], basil [127], strawberry [32,33], and apple [128,129]. Edible plants that have been biofortified with Se [105] or livestock fed selenium-enriched alfalfa [25,130] are used to support human health as reported by the Finnish experience in biofortification with Se through fertilizers.…”
Section: Biofortification Of Cereal Crops: Wheat Rice and Maizementioning
confidence: 99%
“…The most important nutrients that have been investigated in several biofortification studies include calcium [106], iron [92,107], copper [108], zinc [109][110][111], iodine [29,92], potassium [112], and selenium [66,113]. The use of Se fertilizers is one of the most common methods for Se-biofortification of several crops [105], such as rice [113][114][115], maize [116,117], wheat [92,111,118], cowpea [119], potato [85,120], carrot [90,121], turnip [122,123], shallot [124], beans [125], lettuce [91,126], basil [127], strawberry [32,33], and apple [128,129]. Edible plants that have been biofortified with Se [105] or livestock fed selenium-enriched alfalfa [25,130] are used to support human health as reported by the Finnish experience in biofortification with Se through fertilizers.…”
Section: Biofortification Of Cereal Crops: Wheat Rice and Maizementioning
confidence: 99%
“…It is also important for photosynthesis and respiration (Kim and Guerinot, 2007). Li et al (2018) reported that when Se is applied to the plants, it increases the concentration of iron. He et al (2007) also reported that application of Se in lettuce had increased mineral content.…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies have been conducted worldwide ( Alfthan et al., 2015 ; Grant et al., 2007 ; McLaren and Clucas, 2006 ; Yan et al., 2021 ; Yuan et al., 2022 ), this strategy is mainly used in Finland, where the problem of Se deficiency in soil is widespread. Biofortification can be carried out in different ways, such as application on leaves ( Graham, 2018 ; Kápolna et al., 2007 ; Ros et al., 2016 ; Xiong et al., 2018 ) or directly in the ground ( Broadley et al., 2010 ; Larsen et al., 2006 ; Ros et al., 2016 ).…”
Section: Biofortificationmentioning
confidence: 99%